An introduction to the counseling profession - Brown, Duane; Srebalus, David J. (Englewood Cliffs, N.J : Prentice-Hall, 1988)
An introductory text designed to present students entering the field of counselling with a sense of the profession they are choosing. It covers history, major theories, techniques, and procedures used by counsellors.
Includes bibliographies and indexes.
Keywords: Counseling -- Vocational guidance; Counselling